The magic school bus and the electric field trip - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1997)
Ms. Frizzle takes her class on a field trip through the town's electrical wires so they can learn how electricity is generated and how it is used.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal, November 1997.
Booklist, October 1997.
Horn Book, January 1998.
Kirkus Review, September 1997.
Keywords: Electric power -- Juvenile literature; Electric power distribution -- Juvenile literature; Electricity; Electric power; Electricity; Electric power; Electric power; Electricity